Difusi Inovasi Aplikasi Clubhouse pada Mahasiswa Ilmu Komunikasi FISIP Universitas 17 Agustus Surabaya - Dewi Sri Andika Rusmana; Irmasanthi Danadharta (Universitas Merdeka Malang, 2022)
The Covid-19 pandemic has changed the teaching and learning process from traditional to digital. This abrupt change caused a high level of stress among the students. One way to decrease student’s stress level is to seek entertainment or actively doing their preferred hobbies. Downloading an entertaining application into their gadgets is one of the things they do. Clubhouse is an audio-chat application created in 2020 but gain popularity in 2021. This research aims to dig student’s adaptation process in using the Clubhouse application as a part of the Communication Process. This research used Qualitative Descriptive Method together with Innovation Diffusion Theory Approach. Data Collecting was done to six university students of Department of Communication Science major in FISIP 17 Agustus 1945 Surabaya University who uses Clubhouse. The result showed that the informants adaptation progress began from knowing the application through social media, looking for information and directly using, understanding the positives and negatives till deciding to accept or reject the application. Among the informants, two refused while four accepted the application although two informants confirms that they will no longer use Clubhouse until there are significant new features and upgrades.Keywords: Clubhouse Application, Innovation Diffusion, University Students